2015
DOI: 10.1128/jvi.00610-15
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic Choriomeningitis Virus Differentially Affects the Virus-Induced Type I Interferon Response and Mitochondrial Apoptosis Mediated by RIG-I/MAVS

Abstract: IMPORTANCEArenaviruses are important emerging human pathogens that are maintained in their rodent hosts by persistent infection. Persistent virus is able to subvert the cellular interferon response, a powerful branch of the innate antiviral defense. Here, we investigated the ability of the prototypic arenavirus lymphocytic choriomeningitis virus (LCMV) to interfere with the induction of programmed cell death, or apoptosis, in response to superinfection with cytopathic RNA viruses. Upon viral challenge, persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 51 publications
1
20
0
2
Order By: Relevance
“…Intriguingly, arenaviruses appear to be highly selective in their antagonism of these innate immune pathways. For example, Pythoud et al demonstrated that despite blocking RIG-I/MAVS-dependent type I IFN production, LCMV leaves MAVS-dependent apoptosis fully functional (47). Likewise, we report here that JUNV can block activated PKR from phosphorylating eIF2␣ ( Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Intriguingly, arenaviruses appear to be highly selective in their antagonism of these innate immune pathways. For example, Pythoud et al demonstrated that despite blocking RIG-I/MAVS-dependent type I IFN production, LCMV leaves MAVS-dependent apoptosis fully functional (47). Likewise, we report here that JUNV can block activated PKR from phosphorylating eIF2␣ ( Fig.…”
Section: Discussionsupporting
confidence: 78%
“…The small (S) segment encodes for the viral glycoprotein precursor (GPC) and the viral nucleoprotein (NP). GPC is co-translationally cleaved by signal peptidase to produce a stable 58 amino acid Stable Signal Peptide (SSP) and GPC that is post-translationally processed by the cellular Site 1 Protease (S1P) to yield the two mature virion GP1 and GP2 glycoproteins that together with SSP form the GP complex involved in receptor binding and virus cell entry (Beyer et al, 2003; Buchmeier et al, 2007; Pinschewer et al, 2003; Rojek and Kunz, 2008; Rojek et al, 2008), NP, is the most abundant viral protein in infected cells and virions (Buchmeier et al, 2007) and performs multiple roles during infection, including encapsidation of the viral genome RNA species to form, together with L, the viral ribonucleoprotein (vRNPs) complex that directs the biosynthetic processes of RNA replication and gene transcription of the viral genome (Lee et al, 2000; Ortiz-Riano et al, 2012a, 2012b), and inhibition of the cellular type I interferon (IFN-I) (Borrow et al, 2010; Martinez-Sobrido et al, 2006, 2007, 2009, Pythoud et al, 2012, 2015) and inflammatory (Borrow et al, 2010; Lee et al, 2000; Rodrigo et al, 2012) responses.…”
Section: Introductionmentioning
confidence: 99%
“…genome, is recognized by TLR-3 (double-stranded RNA [dsRNA]), TLR-7 and TLR-8 (ssRNA), RIG-I (5= triphosphate ssRNA), and NLRP3 (5). Lymphocytic choriomeningitis virus (LCMV), the prototype member of the Arenaviridae family, which contains a negative-sense genome comprised of two ssRNA viral segments, is mainly recognized by TLR-7, RIG-I, and melanoma differentiation-associated gene 5 (MDA-5) (6). Coronaviruses (CoVs) are positive-sense ssRNA viruses recognized by MDA-5, TLR-7, and RIG-I (7)(8)(9).…”
mentioning
confidence: 99%